(untitled) (Italiano LinguaDue, 2025)
Mi propongo di fare il punto sulle due principali questioni che sono state sollevate a proposito del cosiddetto “sessismo” della lingua italiana: quindi da una parte la femminilizzazione dei nomi di cariche e professioni; dall’altra il dibattito sul genere maschile cosiddetto non marcato, quando considerato inclusivo o sovraesteso. I due temi sono indagati a partire dall’assetto morfo-sintattico dell’italiano, che rende possibili o al contrario difficilmente praticabili le soluzioni via via individuate. Reflections on grammatical gender and inclusive language: where are we at? I propose to take stock of the two main issues that have been raised regarding the so-called "sexism" of the Italian language: on the one hand the feminization of titles and names of professions; on the other hand, the debate on the so-called unmarked male gender, when considered inclusive or overextended. The two themes are investigated starting from the particular morpho-syntactic structure of Italian, which makes the various solutions identified possible to adopt, or else difficult or practically impossible.